Adsorption of Mercury(II) Ions by Poly(Hydroxyethylmethacrylate) Adsorbents with Thiazolidine Groups - Ç. Arpa; A. Sağlam; S. Bektał; S. Patir; Ö. Genç; A. Denizli (Adsorption Science & Technology)
A wide variety of adsorbents has been reported in the literature for heavy metal adsorption. We have recently developed a new polymer system for the removal of contaminant heavy metal ions from aquatic systems. Thus, poly(hydroxyethylmethacrylate) (PHEMA) microbeads carrying thiazolidine (0.318 mmol/g) were prepared for the removal of different amounts of mercury(II) ions (50–900 mg/l) from aqueous solutions and at different pH values (3.0–7.0). Adsorption rates were high with adsorption equilibria being reached within 10 min. The adsorption of Hg(II) ions on to the thiazolidine-immobilized microbeads from single solutions amounted to 1.11 mmol/g. The formation constant of the thiazolidine–metal ion complex was investigated by the method of Ružić. The calculated value of the stability constant was 9.11 × 10 5 l/mol for the Hg(II)–thiazolidine complex. PHEMA microbeads carrying thiazolidine may be regenerated by washing with a solution of hydrochloric acid (0.05 M). The maximum desorption ratio was as high as 99%. These PHEMA microbeads may be used repeatedly for more than three adsorption/desorption cycles without any considerable loss in adsorption capacity.